Prognosis of elite basketball players after an Achilles tendon rupture - Siu, R.; Ling, S. K. K.; Fung, N.; Pak, N.; Yung, P. S. H. (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2020)
Objective: Professional Basketball players are at high risk of Achilles tendon rupture. Despite this, there remains limited research into the factors affecting rehabilitation and the long term outcomes of these players. Our aim is to quantify the effect of a player`s Achilles tendon rupture on their post-injury performance, and also to explore for correlations between their recovery timeline and pre-injury characteristics. Creation of an injury timeline of past incidents will allow injured players to better track their progress and also inform them about the probable impact on their careers. Hypothesis: Players with Achilles tendon rupture injury will exhibit decreased performance compared to their pre-injury self and their non-injured peers after recovery. Methods: Professional basketball players who sustained a unilateral Achilles tendon rupture from 1992 to 2016 were collected. 12 players met our inclusion criteria and their Player Efficiency Ratings (PER) were obtained as primary outcome measures; matched controls were chosen based on the PER, Age and playing position. The players` index season PER was compared against the PER during the 10 games immediately following the players` return and the PER of their post-injury peak performing season. The same data analysis was performed against their control group. To investigate the factors affecting the recovery and long-term consequences of their injury, we correlated the variables of Age, BMI, Time of Injury and pre-injury PER with the player`s time to return to play and their post-injury PER. Results: 2 out of 12 players failed to return to playing in the elite professional league following an Achilles Tendon Rupture, others returned after a mean recovery time of 10 months. When compared to players` index PER, the mean PER reduction during the 10 games immediately following the players` return was 7.15 (P < .000). Players on average took 1.8 seasons to reach their post-injury peak performance, with only 1 player returning to his pre-injury performance. Others suffered a mean PER reduction of 3.5 (P = .004) when compared to their index PER and 5.4 (P = .045) against their matched controls. Conclusion: Achilles tendon rupture can be a career-ending injury for professional basketball players. They are expected to miss 10 months for rehabilitation and reach their post-injury peak performance level at the 2nd season back. The post-injury peak performance is significantly worse than the pre-injury level, but is similar to matched non-injured players.